2017
DOI: 10.28971/532017cl106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Nurse Knowledge and Attitudes of Early Mobilization of the Postoperative Patient

Abstract: Mobilization plays an important role in the outcomes of postoperative patients. Early mobilization as an intervention is the most significant general nursing measure in the prevention of complications. Current research demonstrates a decrease in complication rates, reported pain and length of stay when early ambulation is initiated. Despite this evidence, early mobilization as a best practice standard is implemented inconsistently on the women's health unit of a community hospital. The purpose of this project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The MISSCARE Survey of 1098 nurses in four US hospitals revealed that among 21 elements of nursing care surveyed, ambulation had the highest percentage (86.6%) of being not practised noted by the nurses. 7 As per a study by Clement I 8 done in 2014 in Kempagowda Institute of Medical Sciences, Bangalore on 150 abdominal surgery patients, it was found that there was a significant difference in the post-test scores of activities of daily living, functional activity, and psychological wellbeing between the study group and control group. It is also noted that early mobilisation was not adequately practised in my study setting due to multiple reasons leading to complications like inadequacy in feeding and elimination, occurrence of complications like gastrointestinal dysfunction or discomfort, and increased dependence onpain killers.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The MISSCARE Survey of 1098 nurses in four US hospitals revealed that among 21 elements of nursing care surveyed, ambulation had the highest percentage (86.6%) of being not practised noted by the nurses. 7 As per a study by Clement I 8 done in 2014 in Kempagowda Institute of Medical Sciences, Bangalore on 150 abdominal surgery patients, it was found that there was a significant difference in the post-test scores of activities of daily living, functional activity, and psychological wellbeing between the study group and control group. It is also noted that early mobilisation was not adequately practised in my study setting due to multiple reasons leading to complications like inadequacy in feeding and elimination, occurrence of complications like gastrointestinal dysfunction or discomfort, and increased dependence onpain killers.…”
Section: Introductionmentioning
confidence: 93%
“…Post-operative ambulation promotes the return of gut function assisting in the prevention of post-operative ileus. 7 Nurses play an important role in the early ambulation of post-operative patients. The MISSCARE Survey of 1098 nurses in four US hospitals revealed that among 21 elements of nursing care surveyed, ambulation had the highest percentage (86.6%) of being not practised noted by the nurses.…”
Section: Introductionmentioning
confidence: 99%
“…(Masse, 2017) To decrease the incidence of these complications, several studies highlighted that, practicing postoperative early ambulation in elderly patients with abdominal surgery promotes clearance of thick secretions and production of surfactant, improving lung expansion and decreases hypoventilation. As well as responsible for 71% reduction of postoperative RTIs Chatterley, L. (2017). It also gives positive results on both physical and psychological status and help elderly to return to their activities of daily living within a shorter period of time (Sabate, 2014).…”
Section: Introductionmentioning
confidence: 99%